PENDUGAAN UMUR SIMPAN GULA SEMUT DALAM KEMASAN DENGAN PENDEKATAN ARRHENIUS (Shelf Life Prediction of Palm Sugar on Packaging using Arrhenius Equation) - Hary Kurniawan; Nursigit Bintoro; Joko Nugroho W.K. (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
The purpose of this research was to determined the shelf life of packaged palm sugar at various temperatures and relative humidity (RH) storage using Arrhenius model based on changes in water content. The palm sugars were packed with 0.675 mm polyethylene packaging and stored at 15, 25, 30 and 35°C at RH of 77% and 98%. Measured parameters included the determination of critical parameters of palm sugar, initial moisture content and critical moisture content of palm sugar, changes in moisture content during storage. The Arrhenius model approach was used in this study to predict the shelf life period of palm sugar. The results showed that the texture was one of palm sugar critical parameters. Initial moisture content and critical moisture content of palm sugar were obtained at 1.51% (db) and 6.80% (db), respectively. Increase in moisture content of palm sugar occurred in various temperature variations and RH storage. The higher the storage temperature, the higher the moisture content of the palm sugar, which was characterized by the greater slope of moisture content relationship graph with respect to storage period at both RH 77% and 98%. The longest duration of palm sugar occurredat 15°C, RH 77%; the shortest duration occurred at 35°C, RH 98%. Keywords: palm sugar, packaging, relative humidity, temperature, shelf life ABSTRAK Tujuan dari penelitian in adalah menentukan umur simpan gula semut dalam kemasan pada berbagai suhu dan RH penyimpanan mengunakan model Arrhenius berdasarkan perubahan kadar air. Gula semut dikemas menggunakan kemasan polietilen ketabalan 0,675 mm dan disimpan pada suhu 15, 25, 30 dan 35oC pada RH 77% dan 98%. Parameter yang diukur antara lain penetuan parameter kritis gula semut, kadar air awal dan kadar air kritis gula semut, perubahan kadar air selama penyimpanan. Pendekatan model Arrhenius digunakan dalam penelitan ini untuk memprediksi umur simpan gula semut. Hasil menunjukkan bahwa tekstur merupakan salah satu parameter kritis gula semut. Kadar air awal dan kadar air kritis gula semut diperoleh masing-masing 1,51 % (db) dan 6,80% (db). Terjadi peningkatan kadar air gula semut pada berbagai variasi suhu dan RH penyimpanan. Semakin tinggi suhu penyimpanan maka kenaiakn kadar air gula semut semakin besar yang ditandai dengan semakin besar kemiringan grafik hubungan kadar air terhadap waktu penyimpanan baik pada RH 77% dan 98%. Umur simpan gula semut paling lama terjadi pada suhu 15oC RH 77% dan umur simpan gula semut yang paling pendek terjadi pada suhu 35oC RH 98%. Kata kunci: gula semut, kelembaban relatif, kemasan, temperatur, umur simpan